2018
DOI: 10.1001/jamainternmed.2017.4831
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Left Ventricular Assist Devices Among Recipients With and Without End-stage Renal Disease

Abstract: IMPORTANCE Left ventricular assist devices (LVADs) are widely used both as a bridge to heart transplant and as destination therapy in advanced heart failure. Although heart failure is common in patients with end-stage renal disease (ESRD), little is known about outcomes after LVAD implantation in this population.OBJECTIVE To determine the utilization of and outcomes associated with LVADs in nationally representative cohorts of patients with and without ESRD. DESIGN, SETTING AND PARTICIPANTS We described LVAD u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 28 publications
2
78
1
Order By: Relevance
“…Bansal et al recently published an analysis of circulatory support use in people with ESRD from 2003 to 2013, based on Medicare claims 28. However, unlike our analysis, that analysis included both external circulatory support devices ( ICD‐9‐CM 37.62 and 37.65) and implantable VADs 28, 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bansal et al recently published an analysis of circulatory support use in people with ESRD from 2003 to 2013, based on Medicare claims 28. However, unlike our analysis, that analysis included both external circulatory support devices ( ICD‐9‐CM 37.62 and 37.65) and implantable VADs 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Bansal et al recently published an analysis of circulatory support use in people with ESRD from 2003 to 2013, based on Medicare claims 28. However, unlike our analysis, that analysis included both external circulatory support devices ( ICD‐9‐CM 37.62 and 37.65) and implantable VADs 28, 29. Thus, temporary circulatory support devices were included, which have different indications and outcomes than durable VADs, including placement in dire circumstances such as acute cardiogenic shock or cardiopulmonary arrest 30.…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits are substantial, the complexity of the operation in the setting of advanced heart failure is challenging and can result in significant end-organ dysfunction, complicating the perioperative course and long-term survival. Whereas numerous studies have examined the outcome of durable VAD implantation in the setting of renal dysfunction or dialysis, [1][2][3][4] few have focused on the impact of durable VAD implantation on the incidence of new acute kidney injury.…”
Section: Francis D Pagani Md Phdmentioning
confidence: 99%
“…Bansal et al reported on a United States Renal Data System dataset on patients with end stage kidney disease that underwent placement of left ventricular assist devices. After adjustment for several relevant confounders, the adjusted risk of death was markedly increased (HR = 36.3; 95% CI 15.6–84.5), with most subjects surviving for less than 3 weeks [23]. In contrast, Walther et al [24] reported an HR of 2.3 (95% CI 1.4–3.8) in their analysis of the National Inpatient Sample for the same question.…”
Section: Advanced Heart Failure Therapies and Kidney Disease Outcomesmentioning
confidence: 99%